PERENCANAAN JUMLAH PEMESANAN BAHAN BAKU PEMBUATAN LEMARI DENGAN MENGGUNAKAN LOT SIZE WAGNER WITHIN - Muhamad Zulhamsyah Ridwanulloh; Akhsani Nur Amalia; Asep Hermawan (Metode : Jurnal Teknik Industri, 2023)
Inventory is an economically valuable idle resource waiting to be processed, in the manufacturing industry inventory is very crucial, where the lack of inventory will stop the production process. Inventory planning is expected to run effectively and efficiently (optimally) in order to have a large positive impact on the company. The purpose of this study is to use an optimal solution to determine the total cost of inventory and the amount of savings generated based on the comparison between existing conditions and the results of the calculation of wagner within algorithm. Data is obtained by literature study as a way of collecting data and sources related to research and literature review as relevant theoretical sources from journals, books and other documents as sources of information. Data processing and analysis is carried out using material requirement planning with lot size wagner within algorithm technique. The results of raw material inventory planning with wagner within algorithm obtained results with large savings for three types of products, including type B products of 77.96%, APMS type 80.89%, and type C 73.41%.